2019
DOI: 10.2478/raon-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

CT findings predict survival of patients with peripheral T cell lymphoma: a preliminary study

Abstract: Background Peripheral T-cell lymphoma (PTCL) is an uncommon disease with poor clinical outcomes. Radiological reports on the survival of patients with PTCL are scarce. The purpose of this study is to investigate the prognostic value of CT findings to predict clinical outcomes in fifty-one patients with histologically proven PTCL. Patients and methods The clinical data and CT images of all patients were retrospectively reviewed. CT features including number of involvement sites, lesion size, shape, margin, den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…[26] observed a worse therapy outcome for large mediastinal masses. Yang et al [11] showed a correlation between inhomogeneous density in the tumor pattern and a poor survival outcome in 51 NHL patients. Analogue changes in MRI associated with necrosis in nasopharyngeal carcinoma are an established prognostic factor [24].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] observed a worse therapy outcome for large mediastinal masses. Yang et al [11] showed a correlation between inhomogeneous density in the tumor pattern and a poor survival outcome in 51 NHL patients. Analogue changes in MRI associated with necrosis in nasopharyngeal carcinoma are an established prognostic factor [24].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Although it has been postulated by Hopper and Yang [9,11] there are no larger studies that histologically correlate HDV to necrosis.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…According to prior studies using whole-body CT 15 and 18 F-fluorodeoxyglucose positron emission tomography/CT, 16,17 tumor necrosis was an independent predictor for worse prognosis in DLBCL. Prior studies that evaluated whole-body CT findings of peripheral T-cell lymphoma 18 and CT and MR imaging findings of untreated extranodal non-Hodgkin lymphoma of the head and neck region 7 found that an ill-defined margin of the primary lesion was a valuable prognostic factor to predict the worse clinical outcomes. An ill-defined margin in extranodal primary lesions of the head and neck region indicated a high risk of relapse or metastasis within 2 years after therapy and an unfavorable survival outcome for non-Hodgkin lymphomas 7 …”
Section: Discussionmentioning
confidence: 99%
“…7 However, in the present study, there were no significant differences in necrosis or ill-demarcated margin between the good and poor outcome groups. The prior reports assessing prognostic imaging features of lymphoma were conducted on DLBCL in any organ, [15][16][17] peripheral T-cell lymphoma in any organ, 18 or extranodal non-Hodgkin lymphoma in the head and neck region, 7 whereas this study was conducted only on nodal DLBCL and FL in the head and neck region. Although 19 patients with non-Hodgkin lymphoma except for DLBCL or FL were excluded from this study, peripheral T-cell lymphoma 18 or any histological subtype of non-Hodgkin lymphoma 7 were included in the prior reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation